Role of HMGB1 in regulation of STAT3 expression in CD4(+) T cells from patients with aGVHD after allogeneic hematopoietic stem cell transplantation - Xu, Ya-Jing (Clinical immunology (Orlando, Fla.), 2015)
Copyright © 2015 The Authors. Published by Elsevier Inc. All rights reserved.